2021
DOI: 10.5194/egusphere-egu21-5485
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sources and pathways of biocides and their transformation products in 2ha urban district

Abstract: <p>Biocides used as film protection products to prevent algae and fungi growth on facades wash off during rain events and represent a potential risk to the environment. So far, urban monitoring studies focused mainly on large heterogeneous urban areas. Thus, little information about individual sources and entry pathways were obtained. However, this is important to understand the potential risk of biocide entry to groundwater.</p><p>This study investigates biocide emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Some well-known biocides found in construction materials include isoproturon, diuron, carbendazim, terbutryn, and others. [7,[10][11][12]. The concentration of these chemicals in façade runoff is high in the early lifetime of the painting material and decreases with increasing exposure time.…”
Section: Introductionmentioning
confidence: 99%
“…Some well-known biocides found in construction materials include isoproturon, diuron, carbendazim, terbutryn, and others. [7,[10][11][12]. The concentration of these chemicals in façade runoff is high in the early lifetime of the painting material and decreases with increasing exposure time.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] Emissions of biocides from urban environments have been evidenced and characterized in a few studies but they were generally restricted to a small scale, a limited number of compounds, and a targeted emission process. 5,9,11,15,17,18 Numerous studies [18][19][20][21][22][23] focused on leaching from biocidetreated building materials during rainfall events and showed that rain intensity and wind direction were the main influencing factors for this process. After being leached from buildings, biocides can reach surface waters through runoff/ stormwater 5,11,17,18 or groundwater through infiltration.…”
Section: Introductionmentioning
confidence: 99%
“…After being leached from buildings, biocides can reach surface waters through runoff/ stormwater 5,11,17,18 or groundwater through infiltration. 12,22 Up to now, urban inputs of biocides to the receiving environments have generally been modelled by considering emission factors from building materials. 2,6,19,20 This may have overlooked other sources of biocides such as indoor household uses.…”
Section: Introductionmentioning
confidence: 99%